ПРАВОВЕ ЗАБЕЗПЕЧЕННЯ РЕАЛІЗАЦІЇ НАЦІОНАЛЬНИХ ПРОЕКТІВ: ОКРЕМІ ПИТАННЯ - Hrytsenko, G.M. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2012)
The paper deals with some theoretical and practical moments of implementation of national projects and problems hindering their successful implementation, including the problems connected with corresponding legislation. Based on analysis of the world trends, the promising model of national projects implementation is identified, and the changes to be made in the legislation are offered.